2016
DOI: 10.3168/jds.2016-11306
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Follicle superstimulation before ovum pick-up for in vitro embryo production in Holstein cows

Abstract: The objective was to evaluate in vitro embryo production (IVEP) in nonlactating Holstein cows after ovarian superstimulation. Cows were randomly assigned in a crossover design to 1 of 2 groups: control (n=35), which was not synchronized and not treated with hormones before ovum pick-up (OPU), or hormone-treated (n=35), in which wave emergence was synchronized and animals treated with porcine (p)-FSH in the presence of norgestomet before OPU. In the hormone-treated group, all follicles ≥7mm in diameter were asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In the present study, we demonstrated the transcriptional differences generated by superstimulation using eCG combined with FSH on immature COCs and blastocysts from superstimulated Nelore cows. Although our results corroborated the findings of L. H. Oliveira et al () and showed that neither superstimulatory treatment affected blastocyst rates, we found several differences in COCs and blastocysts gene expression profiles between the superstimulatory treatments.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we demonstrated the transcriptional differences generated by superstimulation using eCG combined with FSH on immature COCs and blastocysts from superstimulated Nelore cows. Although our results corroborated the findings of L. H. Oliveira et al () and showed that neither superstimulatory treatment affected blastocyst rates, we found several differences in COCs and blastocysts gene expression profiles between the superstimulatory treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Although administration of FSH prior to OPU has been a common practice for increasing the numbers of follicles available for OPU, most studies have adopted the conventional twice daily treatments with FSH, with either positive results in the number of COCs collected and embryos produced (Ongaratto et al, 2011;Blondin et al, 2012;Vieira et al, 2014; or no effect on COC or embryo production in Holstein cows (Oliveira et al, 2016). Obviously, the possibility of giving a single FSH injection instead of four prior to OPU in genetically superior animals is critically important for the widespread application of this technology in commercial herds, where personnel are not as familiar with intensive treatment protocols as producers working with purebred cattle.…”
Section: Manipulation Of Follicular Development For In Vitro Embryo Pmentioning
confidence: 99%
“…Use of gonadotropin hormones before OPU, can increase the ratio of follicles with intermediate diameters (>6 and <10 mm) in the ovary (Goodhand et al 1999). Therefore, gonadotropin applications during follicular development can be used to achieve ideal follicles for IVEP (Oliveira et al 2016). Three different gonadotropins are used for ovarian superstimulation in cattle.…”
Section: Ovarian Superstimulationmentioning
confidence: 99%